Can we predict occurrence of febrile convulsions in children with fever by increased neutrophil-to-lymphocyte ratio and C-reactive protein? - Rajakumar Marol,; Rohitkumar Marol,; Sharanabasappa Matti,; Renuka Marol, (Indian Journal of Child Health, 2020)
Background: Febrile seizure (FS) is the most common seizure disorder in children and is a major challenge in pediatric practice because of its high incidence in young children, a lack of predictive indications and their tendency to recur. Age at first seizure, male sex, and family history of FS, duration of fever, and height of temperature are the only significant risk factors presently known for predicting FSs. Objectives: The objectives of the study were to determine whether alterations in basic laboratory parameters such as neutrophil-to-lymphocyte ratio (NLR) and serum C-reactive protein (CRP) are associated with first episode of FS in children. Materials and Methods: This retrospective observational study was conducted in a level 2 pediatric hospital. A total of 196 children between the age of 6 months and 60 months who presented with first episode of febrile convulsions constituted the study group (FS cases). A total of 196 febrile children who presented only with fever within the same time period were selected as controls. NLR, CRP, and other basic laboratory parameters were compared between FS cases and controls. Results: NLR and CRP were both higher among FS than controls. Median of NLR in FS and controls was 1.55 and 0.67 (p